Company value analysis: Empirical evidence from Western Europe - Bojana Vukovic; Kristina Peštović; Dušan Saković; Teodora Ilić (Anali Ekonomskog fakulteta u Subotici, 2025)
The assessment of the future sustainability of the company is based on the analysis of its value. In order to find the best way to maximize value and improve corporate performance, this paper aims to research factors that determine the value of Western European companies in the time period 2017-2022. The influence of financial determinants such as financial leverage, profitability, size, liquidity, growth, and dividend payout ratio on company value was thoroughly analyzed. The research is based on a sample of 321 companies, creating 1926 observations. To process the data, panel regression analysis is used. Research results presented that leverage and profitability have a positive impact of statistical significance, while company size and liquidity have the opposite impact of statistical significance. Indicating the positive and negative impact of the analyzed indicators on the value of the company creating a basis for the optimal use of available funds, strengthening the competitive position, and meeting the information needs of all internal and external stakeholders.